Sri Aman District Council / Roselina Dian - Dian, Roselina (University Technology MARA Sarawak, 2013)
Sri Aman was a market town and port, and the capital of Sri Aman District and Sri Aman Division in Sarawak, east Malaysia. It’s also called Bandar Sri Aman and was formerly known as Simanggang. The name had been change from Simanggang to Sri Aman. The name of Sri Aman “town of Peace” in the Malay language. It was located on the Lupar River; it was 193 kilometer, a three-hour drive from Kuching, and also the capital of Sarawak. It was means trade center for the timber, oil palm, rubber and pepper of its mostly agricultural district. Sri Aman was a famous for the Benak or tidal bore of the Batang Lupar River. Tidal bore cames in from the river mouth and filled up the river very rapidly in the course of about ten minutes. The wave crest at Sri Aman was up two to three meters high. This was one approximately 400 rivers and estuaries in the world where this phenomenon happened. There were time table at the river which had the time and dates for when the tidal bore will occur, but the really big ones occurred only couple of times a year. On this year, tidal bore will happened again in the month of October. Sri Aman also a gateway for tourists to the Batang Ai National Park, and Cultural tours to the Iban longhouses along the river.